De Novo Donor-Specific HLA Antibody Development and Peripheral CD4+CD25high Cells in Kidney Transplant Recipients: A Place for Interaction? - Josefina Alberu; Maria Inés Vargas-Rojas; Luis E. Morales-Buenrostro; Jose C. Crispin; Roxana Rodríguez-Romo; Norma O. Uribe-Uribe; Gabriel Carrasco; Diana Gómez-Martín; Jorge Alcocer-Varela (Journal of Transplantation)
The aim of this study was to determine whether the abundance of regulatory T cells (Tregs) (CD4+CD25high) affects the de novo development of anti-HLA donor-specific antibodies (DSAs) in kidney transplant recipients (KTRs). Methods. Unsensitized (PRA ≤ 10%, no DSA) adult primary KTRs who received a living (83%) or deceased (17%) KT in our Institution during 2004/2005 were included. DSA testing was performed monthly, and Tregs were quantified by flow cytometry every 3 months, during the 1st year after KT. All patients received triple drug immunosuppressive therapy (CNI + MMF or AZA + PDN); 83% received anti-CD25. Results. 53 KTRs were included; 32% developed DSA during the 1st year after KT. Significantly lower 7-year graft survival was observed in those who developed DSA. No difference was observed in Treg numbers up to 9 months after KT, between DSA positive and negative. However, at 12 months after KT, DSA-negative patients had significantly higher numbers of Treg. Conclusions. Early development of DSA was not associated to variations in Treg abundance. The differences in Treg numbers observed at the late time point may reflect better immune acceptance of the graft and may be associated to long-term effects. Additional inhibitory mechanisms participating earlier in DSA development after KT deserve to be sought.